Trombone Shorty - Andrews, Troy; Collier, Bryan (New York : Abrams Books for Young Readers, 2015)
c
Caldecott Honor, 2016
Keywords: Andrews, Troy -- Juvenile literature; Andrews, Troy; Jazz musicians -- United States -- Juvenile literature; Jazz musicians -- United States -- Biography -- Juvenile literature; Trombonists -- United States -- Juvenile literature; Trombonists -- United States -- Biography -- Juvenile literature; New Orleans (La.); Autobiographies